Preprocedural Viral Load Effects of Oral Antiseptics on SARS-CoV-2 in Patients with COVID-19: A Systematic Review - Miriam Ting; Alex Dahlkemper; Jeremy J. Schwartz; Manzel Woodfork; Jon B. Suzuki (Biomedicines, 2023)
(1) There are limited clinical trials to support the effectiveness of mouth rinses when used as a preprocedural rinse against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). This systematic review aims to evaluate the efficacy of antiseptic mouth rinses as a preprocedural rinse in reducing SARS-CoV-2 oral viral load in-vivo. (2) Methods: A literature search was conducted through November 2022 for the following databases: PubMed, Web of Science, Cochrane Library, and Google Scholar. The evaluated outcomes were quantitative changes in viral load and the statistical significance of that change after using antiseptic mouth rinses. (3) Results: 14 randomized controlled trials (RCT) were selected for risk of bias assessment and data extraction. (4) Conclusion: Within the limits of this systematic review, preprocedural mouth rinses may significantly reduce SARS-CoV-2 in the mouth, thus, reducing the viral particles available for airborne dispersion. Preprocedural mouth rinses may be an effective strategy for reducing airborne SARS-CoV-2 dispersion in the environment. Their use may be a preventive strategy to reduce the spread of COVID-19 in selected medical and healthcare facilities, including dental clinics. Potential preprocedural mouth rinses are identified for use as an integral part of safe practice for healthcare protocols. This systematic review was registered with the National Institute for Health Research, international prospective register of systematic reviews (PROSPERO): CRD42022315177.